(3GdESYGa aj TQM ThGgO GdHjVGhj hGdcTGas - (3NVQ Hf YWGA Gddg GdehUdj,J (B1007 (3g` s
(3ChdgG (B:s
(3Gddge jG cTGa UHGHI GdChgGe HTehS ThGgO GdYdhe s
(3BNQgG (B:s
(3hGfTO aj GdTYQ GdZQjHG s
(3TQM ajg cJGH GdcTGa ddReNTQi hCfhGQ GdJfRjd ddHjVGhjs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B101s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs